2015
DOI: 10.1097/brs.0000000000000657
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Low Back Pain in Adolescent Patients With Early-Stage Spondylolysis Evaluated Using a Detailed Visual Analogue Scale

Abstract: This study revealed that LBP characteristics may provide important information for distinguishing ESS from other low back disorders. Because early diagnosis is essential for the treatment of ESS, MRI examination is recommended for patients showing severe pain in motion, but less pain when standing or sitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Comparisons of demographic, baseline, and short-term outcomes between those who those of previous work found that males are more likely to experience an acute spondylolysis, in this study, females were more than twice as likely to experience a poor long-term outcome. 1,9,21,26,44 This result is consistent with nonspecific LBP, in which females are more likely to have a poor outcome. 37 Female athlete menstrual characteristics and dietary patterns may be a contributing factor, as is seen in other stress injuries.…”
Section: Limitationssupporting
confidence: 68%
“…Comparisons of demographic, baseline, and short-term outcomes between those who those of previous work found that males are more likely to experience an acute spondylolysis, in this study, females were more than twice as likely to experience a poor long-term outcome. 1,9,21,26,44 This result is consistent with nonspecific LBP, in which females are more likely to have a poor outcome. 37 Female athlete menstrual characteristics and dietary patterns may be a contributing factor, as is seen in other stress injuries.…”
Section: Limitationssupporting
confidence: 68%
“…In addition, some participants of LBP group have reported an intermittent pattern of pain over the last year prior to study; it could be possible that soccer players with chronic LBP (showing LBP for at least 90 days in the past 6 months) might show different results, while our participants did not report such a chronic LBP. Similar to a previous study (8), radiologic assessment of lumbar spine was not a part of this study; however, to rule out other possible LBP etiologies such as spondylolysis (42) or mild scoliosis (43), considering this assessment for future studies is suggested. Finally, our sample size was relatively small and study was undertaken in male soccer players; therefore, the generalizability of the findings to adolescent female soccer populations may be questioned.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity was measured by a Visual analogue scale (VAS: 0–10 cm) [ 43 ] as the average pain during the last week, with 0 indicating “no pain” and 10 “worst pain imaginable”. The VAS is reliable as a measure of pain intensity in children [ 44 ] and is used to detect differences in pain between groups of adolescents [ 45 ]. The pain questionnaire in this study also included two questions about injuries and/ or diseases which could possibly be related to the pain experience.…”
Section: Methodsmentioning
confidence: 99%